Expectation of Tertiary Students of Bangladesh from ELT Classrooms - Haque, Saifa (Journal of NELTA, 2015)
Expectation influences motivation and performance in Second Language Acquisition (SLA). Students’ expectation also plays a significant role in curriculum development. This paper focuses on the expectations of the students in an English language classroom and how they want to be taught. From a study on 45 students of Stamford University Bangladesh, the researcher tried to find students’ expectations about content, factors behind the expectations and effects of expectations in a language classroom using semi-structured interviews. It was found that students have expectations regarding their course content, teaching-learning style and education management. Several factors such as professional need, education background, social beliefs, personal goals and personality of the students worked behind their expectations and their expectations played a significant role in their classroom behavior and performance. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12080 Journal of NELTA, Vol 19 No. 1-2, December 2014: 56-64